Tunable poly(methacrylic acid‐co‐acrylamide) nanoparticles through inverse emulsion polymerization. Issue 6 (6th March 2018) - Zhong, Justin X.; Clegg, John R.; Ander, Eric W.; Peppas, Nicholas A.
Abstract: Environmentally responsive biomaterials have played key roles in the design of biosensors and drug delivery vehicles. Their physical response to external stimuli, such as temperature or pH, can transduce a signal or trigger the release of a drug. In this work, we designed a robust, highly tunable, pH‐responsive nanoscale hydrogel system. We present the design and characterization of poly(methacrylic acid‐co‐acrylamide) hydrogel nanoparticles, crosslinked with methylenebisacrylamide, through inverse emulsion polymerization. The effects of polymerization parameters (i.e., identities and concentrations of monomer and surfactant) and polymer composition (i.e., weight fraction of ionic and crosslinking monomers) on the nanoparticles' bulk and environmentally responsive properties were determined. We generated uniform, spherical nanoparticles which, through modulation of crosslinking, exhibit a volume swelling of 1.77–4.07, relative to the collapsed state in an acidic environment. We believe our system has potential as a base platform for the targeted, injectable delivery of hydrophilic therapeutics. With equal importance, however, we hope that our systematic analysis of the individual impacts of polymerization and purification conditions on nanoparticle composition, morphology, and performance can be used to expedite the development of alternate hydrophilic nanomaterials for a range of biomedical applications. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1677–1686, 2018.